1994
DOI: 10.1200/jco.1994.12.2.360
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of vinorelbine and cisplatin versus vindesine and cisplatin versus vinorelbine alone in advanced non-small-cell lung cancer: results of a European multicenter trial including 612 patients.

Abstract: Since our results have demonstrated that NVB-P yields a longer survival duration and a higher response rate than VDS-P or NVB alone, with acceptable toxicity, this combination should be considered a relevant regimen in advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
313
2
7

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 759 publications
(336 citation statements)
references
References 20 publications
12
313
2
7
Order By: Relevance
“…The treatment outcomes of the present study were superior or at least comparable to the results of previous multi-institutional trials of a combination of CPT-11 plus CDDP (Masuda et al, 1998(Masuda et al, , 1999DeVore et al, 1999;Niho et al, 1999). Recently, superiority of 2-drug combinations of one of the newly developed agents, vinorelbine or paclitaxel, with CDDP to the representative CDDP-based chemotherapy in the 1980s such as CDDP plus vindesine or etoposide was reported in prospective randomized trials (Le Chevalier et al, 1994;Bonomi et al, 2000). However, no definitive conclusion was obtained in the 2 Japanese multi-institutional randomized trials comparing CPT-11 plus CDDP with CDDP plus vindesine (Masuda et al, 1999;Niho et al, 1999), although superiority of CPT-11 plus CDDP for stage IV patients was shown by the subset analysis of one trial (Masuda et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment outcomes of the present study were superior or at least comparable to the results of previous multi-institutional trials of a combination of CPT-11 plus CDDP (Masuda et al, 1998(Masuda et al, , 1999DeVore et al, 1999;Niho et al, 1999). Recently, superiority of 2-drug combinations of one of the newly developed agents, vinorelbine or paclitaxel, with CDDP to the representative CDDP-based chemotherapy in the 1980s such as CDDP plus vindesine or etoposide was reported in prospective randomized trials (Le Chevalier et al, 1994;Bonomi et al, 2000). However, no definitive conclusion was obtained in the 2 Japanese multi-institutional randomized trials comparing CPT-11 plus CDDP with CDDP plus vindesine (Masuda et al, 1999;Niho et al, 1999), although superiority of CPT-11 plus CDDP for stage IV patients was shown by the subset analysis of one trial (Masuda et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…16 -19 A large, pivotal European Phase III trial compared single-agent vinorelbine with vinorelbine/cisplatin as well as with the European standard of vindesine/cisplatin. 20 Cisplatin/ vinorelbine significantly improved the response rate compared with cisplatin/vindesine and single-agent vinorelbine (30% versus 19% and 14%, respectively). Median length of survival was also significantly better (40 weeks versus 32 weeks and 31 weeks).…”
mentioning
confidence: 91%
“…9,10 Recently, advances have been made in understanding the biology of hormone-refractory prostate carcinoma, which is elucidating potential targets for new drugs. 11 Vinorelbine is a new semisynthetic vinca-alkaloid derivative with antimicrotubular activity that has shown to be highly effective in small-cell lung cancer compared with vinblastine and vindesine 12,13 and in hormonedependent tumours such as breast cancer. 14 Moreover, it has less neurotoxicity because it has limited effects on the axonal microtubules.…”
Section: Introductionmentioning
confidence: 99%